EXPLORING THE LEVEL OF SELF-CONFIDENCE AMONG STUDENTS WITH DIFFERENT SPEAKING PERFORMANCE - Lestari, Linda Dwi Ayu; Hidayati, Kuni Hikmah; Laeli, Anita Fatimatul (University of Muhammadiyah Malang, 2024)
This study aimed to investigate the variation of students' self-confidence level in their speaking performance in English. Using a qualitative approach, live experiences, and influencing factors related to self-confidence in speaking English were explored. Data were collected through classroom observations, reflective journals, and interviews to get a deep understanding of participants’ perspectives and behavior. This research was conducted at an English course located in Kaliwates, Jember. The sample consists of two male students and two female students, all at the same CEFR level (A2 Elementary), but with varying levels of self-confidence and speaking performance. The results showed that students with low self-confidence can achieve high scores in speaking performance, while students with high self-confidence do not necessarily achieve high scores. They may still receive a low score in speaking performance, even if they have a high level of self-confidence.